2017
DOI: 10.1371/journal.ppat.1006117
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Thermo-Stabilised, Immunogenic Poliovirus Empty Capsids; a Strategy for Non-replicating Vaccines

Abstract: While wild type polio has been nearly eradicated there will be a need to continue immunisation programmes for some time because of the possibility of re-emergence and the existence of long term excreters of poliovirus. All vaccines in current use depend on growth of virus and most of the non-replicating (inactivated) vaccines involve wild type viruses known to cause poliomyelitis. The attenuated vaccine strains involved in the eradication programme have been used to develop new inactivated vaccines as producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 20 publications
4
64
0
1
Order By: Relevance
“…Although the PV57␦ VLPs used here were shown to have stability superior to that of the wt when produced in a mammalian system, the stabilization did not extend to particles expressed in yeast, possibly for the reasons outlined above. However, in preliminary experiments using the thermostable mutants previously characterized by Fox et al (18,20,49), we have shown Pichia to be capable of efficiently producing D antigen. Therefore, we believe that this system has the potential to produce a VLP vaccine not only for a polio-free world but also as a model system for enterovirus VLP vaccine production.…”
Section: Discussionmentioning
confidence: 67%
“…Although the PV57␦ VLPs used here were shown to have stability superior to that of the wt when produced in a mammalian system, the stabilization did not extend to particles expressed in yeast, possibly for the reasons outlined above. However, in preliminary experiments using the thermostable mutants previously characterized by Fox et al (18,20,49), we have shown Pichia to be capable of efficiently producing D antigen. Therefore, we believe that this system has the potential to produce a VLP vaccine not only for a polio-free world but also as a model system for enterovirus VLP vaccine production.…”
Section: Discussionmentioning
confidence: 67%
“…One is the development of an inactivated vaccine based on nonpathogenic poliovirus strains; the other, more ambitious, is focused on making purified VLP-based vaccines, which would not include a poliovirus propagation step at any stage of production. While both approaches address the safety concerns that drive up the cost of manufacturing the original IPV, which relies on the propagation of large quantities of pathogenic poliovirus strains, they both include tedious purification processes and face significant problems of stabilizing labile poliovirus epitopes required for the induction of protective neutralizing antibodies (22,47,48). Moreover, the nonreplicating vaccines are deficient in the induction of the mucosal immune response, which is critical for the interruption of poliovirus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Poliovirus VLPs are unstable and easily convert from a protective D-antigen to an inactivated C-or H-antigen conformation, which does not induce neutralizing antibodies (21). Even if the antigenic stability of VLPs can be increased by introducing mutations into the capsid protein sequence (22), purified VLPs are incapable of inducing a mucosal immune response, just like the original IPV, and scaling up the experimental systems of VLP production and purification to the industrial level may represent a formidable challenge.…”
mentioning
confidence: 99%
“…Furthermore, hyper-attenuated S19 poliovirus strains unable to replicate in humans have been developed at NIBSC [56] and will be used as seeds for IPV production [57] as well as reagents for essential assays requiring the use of live poliovirus that will now be possible to carry out at lower containment levels, such as neutralization assays for seroprevalence studies or characterization of immunoglobulin preparations for medical use [58]. In addition, NIBSC in collaboration with the Universities of Leeds and Oxford and the John Innes Center (JIC) in the UK has made considerable progress in the research and development of non-infectious vaccine-like particles to be used as vaccines in the post-eradication era [53,59].…”
Section: Poliovirus and Other Enterovirusesmentioning
confidence: 99%